Evaluation of Ibuprofen Prolonged Release of Biomedical PLA-PEG-PLA Hydrogel via Degradation Mechanism - Nguyen, Hien Thi-Thanh; Nguyen, Lam Thi-Truc; Ha, Anh Cam; Huynh, Phu Dai (International Journal of Biomaterials, 2023)
A micellar hydrogel has long been considered an intelligent hydrophobic drug delivery material. In this study, synthesized PLA1750-PEG1750-PLA1750 micellar hydrogel aims to encapsulate ibuprofen (IBU) in the core PLA hydrophobic of the micelle and prolong the drug release time by an injectable route. The structure and morphology of the PLA1750-PEG1750-PLA1750 copolymer hydrogel were demonstrated by 1H NMR and TEM data. The hydrogel also achieved a gel state at a high concentration of 25 wt.% under the physiological conditions of the body (37°C, pH 7.4). Besides, the biocompatibility test displayed that the hydrogel slightly affected mice after injection one week and fully recovered after four weeks. Furthermore, the in vitro degradation of the hydrogel showed apparent gel erosion after the first three weeks, which is related to the IBU release rate: slow for the first three weeks and then fast. As a result, the total drug release after three and four weeks was 18 wt.% and 41 wt.%, respectively. However, in the first 24 hours, the amount of the drug released was 10 wt.%, suggesting that the IBU drug diffused from the surface hydrogel to the buffer solution. These show that PLA1750-PEG1750-PLA1750 hydrogel can be a potential IBU drug delivery candidate.